2020
DOI: 10.1021/acsami.0c06597
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Stacking Effect on Small-Molecular Organic Light-Emitting Diodes Prepared with Solution Process

Abstract: The light-emitting layer (EML) is generally prepared by mixing the host and dopant to realize an organic light-emitting diode (OLED). However, phase separation is often observed during the fabrication process to prepare OLEDs, depending on the structure of the host materials. In particular, phase separation because of π−π stacking is frequently observed during thermal annealing for the solution process. The annealing process is required for solvent removal and complete relaxation of the molecule. Hence, the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…However, according to a recent report by Lee et al, the phosphorescent dopant can be quasi-dewet from EML and escape during annealing procedure during solution processes if the thermal stability of the host materials is very low. 3 To conrm such a possibility, we proceeded with differential scanning calorimetry (DSC) analysis of the PCIC material and, in the end, conrmed that the glass transition temperature (T g ) is very low, about 98 C, and the T m is about 234 C (Table 1). So, we performed molecular dynamics simulation to predict how the relative distance between molecules can be changed on series of annealing processes.…”
Section: Analysis Of New Synthetic Green Host Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, according to a recent report by Lee et al, the phosphorescent dopant can be quasi-dewet from EML and escape during annealing procedure during solution processes if the thermal stability of the host materials is very low. 3 To conrm such a possibility, we proceeded with differential scanning calorimetry (DSC) analysis of the PCIC material and, in the end, conrmed that the glass transition temperature (T g ) is very low, about 98 C, and the T m is about 234 C (Table 1). So, we performed molecular dynamics simulation to predict how the relative distance between molecules can be changed on series of annealing processes.…”
Section: Analysis Of New Synthetic Green Host Materialsmentioning
confidence: 99%
“…In this process, the phosphorescent dopant is separated from the host material, resulting in poor thermal stability. In fact, in a previous paper we reported that the red dopant escaped from the host at 150 C. 3 Phosphorescent devices are inherently affected by many triplettriplet annihilation (TTA) or triplet-polaron quenching (TPQ) processes under high current density driving conditions, and these dopant agglomeration can be a major cause of reduced efficiency and lifetime. 4,5 Apart from this problem, the mixing of the hole transport layer (HTL) and emitting layer (EML) interface suppresses the device lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…The root mean square deviation (RMSD) and root mean square fluctuation (RMSF) of ligand‐protein complex backbone were plotted and the stability of the ligand‐protein complex was determined. The analysis of RMSD, RMSF, and hydrogen bonding interactions were performed using the trajectory analysis incorporated in the Desmond [59] …”
Section: Methodsmentioning
confidence: 99%
“…The analysis of RMSD, RMSF, and hydrogen bonding interactions were performed using the trajectory analysis incorporated in the Desmond. [59] …”
Section: Methodsmentioning
confidence: 99%
“…4 In particular, such a phase separation is frequently observed during thermal annealing processes. 5,6 Thus, we need to anneal in the range not more than 20 o C than glass transition temperature (Tg) because there could be a deterioration of the device performances. 7 However, it is not clear why annealing should be performed under those conditions.…”
Section: Introductionmentioning
confidence: 99%